PERANCANGAN SISTEM INFORMASI PELAYANAN PEMBUATAN SURAT ONLINE DI DESA CIANGSANA BEBASIS WEBSITE - Afandi, Irfan Ricky; Pratiwi, Nunik; Rizki, Ali Abdul; Irva, Muhammad; Aulia, Muhammad Fathan (JATI (Jurnal Mahasiswa Teknik Informatika), 2022)
The mail service department at the village office is the part that interacts the most with the village community. Usually, people come to the village office to make a cover letter such as a birth certificate, death certificate, arrival information and moving information. Currently, the service process that occurs at the Ciangsana village office does not yet have a system that can carry out the process of making letters and monitoring letters remotely and processing computerized files and letter data. What is expected in making this research is to design an online letter-making service information system based on a website so that it can help the community and village officials in the process of making letter-making services. Researchers also apply the waterfall method and use a system trial with black box testing. The results of the black box testing show that all system testing has been successful, which means that the website design has been running well. With the website design, can help the community in the manufacturing process and can help village officials, especially the mail service department, in improving performance efficiency because all letter data processing can be done computerized.